2013
DOI: 10.1172/jci69781
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung-like disease is exacerbated by reduced de novo GMP synthesis

Abstract: Hirschsprung disease (HSCR) is a partially penetrant oligogenic birth defect that occurs when enteric nervous system (ENS) precursors fail to colonize the distal bowel during early pregnancy. Genetic defects underlie HSCR, but much of the variability in the occurrence and severity of the birth defect remain unexplained. We hypothesized that nongenetic factors might contribute to disease development. Here we found that mycophenolate, an inhibitor of de novo guanine nucleotide biosynthesis, and 8 other drugs ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 64 publications
6
49
0
Order By: Relevance
“…9,11 In our study, we found that a parity of ≥3 children increases the risk of having a child with HSCR. On subanalysis for child sex, boys show the same pattern, but not girls, perhaps because of the small sample size and lack of power.…”
Section: Figurementioning
confidence: 47%
See 1 more Smart Citation
“…9,11 In our study, we found that a parity of ≥3 children increases the risk of having a child with HSCR. On subanalysis for child sex, boys show the same pattern, but not girls, perhaps because of the small sample size and lack of power.…”
Section: Figurementioning
confidence: 47%
“…6 There have been speculations about the role of hypothyroidism, vitamin A deficiency, and maternal intake of Ibumetin or mycophenolate during pregnancy, but none of these associations have been confirmed. [7][8][9][10][11] The purpose of this study was to investigate the maternal risk factors and perinatal characteristics of HSCR in Sweden.…”
mentioning
confidence: 99%
“…Some medicines cause HSCR-like disease in mice (20). Human epidemiologic studies identifying nongenetic risks for HSCR may lead to new prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal ENCDCs migrate through paraxial mesoderm before entering the bowel, and then migrate in a rostral to caudal direction to colonize the entire fetal bowel ( Figure 1A). Vigorous ENCDC proliferation during migration is important for full bowel colonization (19,20). ENCDCs differentiate into at least 20 neuronal subtypes or enteric glia (21), form ganglia, extend neurites, and establish and refine functional neural circuits to control the bowel (ref.…”
Section: Ens Morphogenesismentioning
confidence: 99%
See 1 more Smart Citation